PREVALENCE OF ANTIBIOTIC-RESISTANT ESCHERICHIA COLI IN SOME DRINKING WATER TREATMENT PLANTS IN BAGHDAD CITY - Fadhil, Heba; Awda, Jasim; Taha, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate antibiotic-resistant genes in Escherichia coli found in drinking water is a global public health concern. The isolation and identification of Escherichia coli in three drinking water treatment plants in Baghdad city was carried out using a mix of biochemical and molecular analysis on selective medium. LacZ gene amplification by Polymerase Chain Reaction was carried out for molecular identification, and the study showed that lacZ was present in each isolate. The molecular method was used to confirm the culture method's findings.  Both the molecular diagnostic and the culture method produced the same results. Applying the McFarland standard and the Kirby-Bauer disk diffusion method, the antimicrobial susceptibility test was done against 14 distinct antibiotics. The most commonly found antibiotics to which the isolates were resistant (80%–100%) were tetracycline, erythromycin, and ampicillin, with a significant difference (p = 0.0001). Multidrug resistance was present in all of the isolates, as they exhibited resistance to a minimum of three agents across the nine antibiotic classes tested. Escherichia coli is defined as showing resistance to three or more classes of antibiotics. The blaM gene was detected in E. coli isolates 12/36 (33.3%) that produce extended-spectrum beta-lactamase (ESBL).